Short‐term tolerance of equine spermatozoa to various abiotic factors. (5th February 2018) - Pérez‐Marín, CC; Requena, FD; Arando, A; Requena, L; Requena, F; Agüera, EI
Contents: The aim of this study was to determine the effects of various abiotic factors, such as light, physical stress (pipetting) and thermal shock, on the quality of fresh and cooled equine sperm. In experiment I, four sperm aliquots were subjected to different light exposures: (i) protected control samples (CTRL), (ii) exposed to UV light at 10 cm (UV10), (iii) exposed to UV light at 20 cm (UV20) and (iv) exposed to laboratory lighting (LAB). In experiment II, four semen aliquots were subjected to repeated pipetting for 0, 10, 20 and 30 times (CTRL, P10, P20 and P30, respectively). In experiment III, four semen aliquots at 15°C were subjected to thermal oscillations: (i) cooled control sperm at 15°C (CTRL), (ii) oscillations of 1.9°C/min to a temperature of 30°C (T30), (iii) oscillations of 1.4°C/min, with the temperature rapidly falling until reaching 1.3°C (T0R) and (iv) oscillations of 1.1°C/min, with the temperature slowly falling until reaching 4.2°C (T0S). The results revealed that after 30 min, UV10 and UV20 sperm samples showed significantly ( p < .05) lower total and progressive motility values, sperm kinematic parameters and mitochondrial potential. After 45 min of exposure, differences were highly significant ( p < .001). No significant differences ( p > .05) were found for pipetting or thermal oscillations. The results suggest that, even if equine sperm samples are not handled in the laboratory under optimal conditions, fresh and cooled equine spermatozoa are able to resist the impact of various abiotic stimuli without any reduction in their quality. This study analyses the effect on normospermic samples, but future research could look at the tolerance that asthenozoospermic equine samples have to these abiotic influences.